2014
DOI: 10.1371/journal.pone.0089541
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Genes Essential for the Survival of Streptococcus pneumoniae in Human Saliva

Abstract: Since Streptococcus pneumoniae transmits through droplet spread, this respiratory tract pathogen may be able to survive in saliva. Here, we show that saliva supports survival of clinically relevant S. pneumoniae strains for more than 24 h in a capsule-independent manner. Moreover, saliva induced growth of S. pneumoniae in growth-permissive conditions, suggesting that S. pneumoniae is well adapted for uptake of nutrients from this bodily fluid. By using Tn-seq, a method for genome-wide negative selection screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 51 publications
2
49
0
Order By: Relevance
“…S. pneumoniae can also be easily cultured from common objects, such as soft toys recently handled by colonized children 20 . Under ambient, nutrient-sufficient conditions, such as in ex vivo human saliva, pneumococci can survive for days 21 . Under nutrient-poor conditions, such as in airway surface fluid, bacterial expression of Ply increases ex vivo survival 16 .…”
Section: Transmission Of S Pneumoniaementioning
confidence: 99%
“…S. pneumoniae can also be easily cultured from common objects, such as soft toys recently handled by colonized children 20 . Under ambient, nutrient-sufficient conditions, such as in ex vivo human saliva, pneumococci can survive for days 21 . Under nutrient-poor conditions, such as in airway surface fluid, bacterial expression of Ply increases ex vivo survival 16 .…”
Section: Transmission Of S Pneumoniaementioning
confidence: 99%
“…27 Furthermore, the genomewide analysis of Streptococcus pneumoniae identified 147 genes needed for survival in human saliva and transmission by droplet spread, including those involved in cell envelope synthesis and cell transport. 28 On an entirely different time scale, the sequencing of Yersinia pestis bacteria isolated from teeth disinterred from the east Smithfield Black Death burial ground in London dating to 1348 showed that the plague strains associated with this pandemic were similar to those currently circulating, although associated mortality was far greater. 29 This is compatible with the idea that the high mortality seen in the medieval plagues (and the sixth century Plague of Justinian 30 ) was more likely to be associated with epidemiological circumstances (overcrowding, poor general health and living conditions) than with bacterial encoded virulence.…”
Section: Glossarymentioning
confidence: 99%
“…48 Genome wide Tn-seq screen revealed that S. pneumoniae requires its peptide transport system AmiACDEF for survival in human saliva, an essential strategy for transmission. 49,50 Regulation of transcription of the adherence mediating cell surface polypeptide CshA by hexa-hepta peptide permease HppA in S. gordonii shows another example. 51 The Gram positive cocci, S. agalactiae, responsible for causing major invasive infection in human newborns, requires 4 peptide permeases for attachment to the host cells and to express its virulence determinants.…”
Section: Gram Positive Pathogensmentioning
confidence: 99%